Prevalence and Risk Factors of Hernia in Patients With Rectus Abdominis Diastasis: A 10-Year Multicenter Retrospective Study - Yuan, Sue; Wang, Honghong; Zhou, Jie (Frontiers in Surgery, 2021)
Objectives: Hernias are very common in RAD patients. This study aimed to identify and compare the risk factors and patterns of hernia between males and females with RAD. Method: We included patients with RAD from six hospitals within the Partners Healthcare System in Massachusetts, U.S.A. between 2009 to 2018. Univariate and multivariable binary logistic regression analyses were used to identify risk factors associated with hernia. Results: Of 1,294 RAD cases, 866 (67%) were female. The risk of RAD in females was 1.9 times greater than that of males. There were 240 males (56.1%) and 310 females (35.8%) having one or more hernia (P < .001). Of 550 hernia cases, 278 males and 175 females had umbilical hernia (28.1% vs 38.3%, P = 0.085). The distribution of hernia type differed between two groups (P < .0001). Multivariate analysis identified that alcohol use (odd ratio [OR] 1.74 ( 1.17 - 2.59); P = .006), depressive disorder (OR 1.90 (1.209 - 2.998); P = .005) were risk factors of coexisting hernia for males with RAD; age (OR 1.51 (1.33 - 1.72); P = .000), smoking/tobacco use (OR 1.66 (1.13 - 2.44); P = .010) were risk factors of hernia for females. Conclusion: The prevalence and risk factors of hernia in females with RAD significantly differentiated from that in males with RAD. Umbilical hernia is an important type of hernia. Alcohol use and depressive disorder in men and age and smoking in women were risk factors of hernias in patients with RAD.